A Description of Formal Reasoning Ability and Its Relationship with Chemistry Learning Outcomes of Grade XI Senior High School Students - Santi, Lusia; Erlina; Sahputra, Rachmat (Universitas Pendidikan Mandalika, 2025)
This study aims to describe students’ formal reasoning ability and its relationship with chemistry learning outcomes among Grade XI students in the Chemistry 1 and Chemistry 3 specialization classes at a public senior high school in Pontianak City during the first semester of the 2024/2025 academic year. The data collection instrument employed was a formal reasoning ability test developed by Burney. The findings revealed that the majority of students’ formal reasoning abilities were categorized as low, with most students still at the concrete and transitional stages. Among the five aspects of formal reasoning, the probabilistic aspect was the most mastered (71%) compared to the others, whereas the combinatorial aspect was the lowest (21%). Although most students achieved the Minimum Mastery Criterion (MMC) in their academic performance, no significant relationship was found between formal reasoning ability and chemistry learning outcomes. This is attributed to the dominance of students who remain at the concrete stage (54.29%), which limits their ability to comprehend abstract chemistry concepts. These findings indicate a mismatch between academic achievement and formal reasoning ability, and highlight the importance of implementing systematic and contextual learning strategies to enhance students’ formal reasoning in understanding chemistry concepts.